Apparatus for cutting food Malaysia. - Shamsuddin, Rosnah (2009)
An apparatus for cutting jelly product such as nata de coco is provided. The product is cut by way of stamping the product. The apparatus comprises a cutter for cutting the product into sections having a plurality of blades arranged to form a plurality of cutting sections.